2011
DOI: 10.1002/stem.766
|View full text |Cite
|
Sign up to set email alerts
|

Nestin- and Doublecortin-Positive Cells Reside in Adult Spinal Cord Meninges and Participate in Injury-Induced Parenchymal Reaction

Abstract: Adult spinal cord has little regenerative potential, thus limiting patient recovery following injury. In this study, we describe a new population of cells resident in the adult rat spinal cord meninges that express the neural stem/precursor markers nestin and doublecortin. Furthermore, from dissociated meningeal tissue a neural stem cell population was cultured in vitro and subsequently shown to differentiate into functional neurons or mature oligodendrocytes. Proliferation rate and number of nestin- and doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
141
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(150 citation statements)
references
References 89 publications
8
141
1
Order By: Relevance
“…Our previous study also showed that progenitor cells in the third ventricle surroundings could be reactivated by local demyelination in the optic chiasm (128,171). Also nestin and DCX-positive cells have been found in the meninges of the brain and spinal cord (138,173). We concluded that there are widespread sources of stem cells in the CNS that can be activated in different pathological situations, especially in MS.…”
Section: Other Germinal Areas Of the Cnsmentioning
confidence: 59%
“…Our previous study also showed that progenitor cells in the third ventricle surroundings could be reactivated by local demyelination in the optic chiasm (128,171). Also nestin and DCX-positive cells have been found in the meninges of the brain and spinal cord (138,173). We concluded that there are widespread sources of stem cells in the CNS that can be activated in different pathological situations, especially in MS.…”
Section: Other Germinal Areas Of the Cnsmentioning
confidence: 59%
“…High concentrations of stem cells are required for the tissue repair technology, such as reconstructed skin. For this purpose, stem cells can be cultured in media [53]. Stem cell therapy holds a great promise for the repair of injured organs, including kidney [54].…”
Section: Is Stem Cell Therapy the Future Of Regenerative Medicine?mentioning
confidence: 99%
“…O f n o t e , u s i n g s i n g l e -c e l l transcriptomics, they also showed that leptomeningeal PDGFRβ + cells generate various types of clusters that exhibited features of pericytic/fibroblastic, endothelial, and microglial lineages in addition to radial glia-like lineages. However, we recently showed that PDGFRβ + pericytes isolated from post-stroke areas, including the leptomeninges, exhibited multipotent stem cell activity and that they give rise to not only neural (e.g., neurons) but also vascular lineages (e.g., endothelial cells and microglia) (11,12 (5,6,19,20). Thus, the leptomeninges should become a new target for treating CNS developmental disorders and diseases.…”
mentioning
confidence: 99%